1995
DOI: 10.1111/j.1365-2796.1995.tb01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of serum lipids and blood pressure during intervention with n‐3 fatty acids was not associated with changes in insulin levels in subjects with combined hyperlipidaemia

Abstract: The atherogenic risk profile was improved with K85 in subjects with combined hyperlipidaemia, but n-3 fatty acids supplementation did not affect glucose/insulin homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 27 publications
5
25
0
1
Order By: Relevance
“…n-3 FATTY ACIDS IN MODERATE HYPERTRIGLYCERIDEMIA concentrations in persons with moderate hypertriglyceridemia. Relative to the placebo treatment, fasting triglycerides were reduced by 27% after the 3.4-g/d dose, consistent with previous reports (12,(42)(43)(44)(45)(46). The percentage reduction achieved was related to the subjects' triglyceride concentrations after the placebo dose so that, on average, the subjects with the highest triglycerides achieved the greatest percentage reduction after the higher dose.…”
Section: Discussionsupporting
confidence: 77%
“…n-3 FATTY ACIDS IN MODERATE HYPERTRIGLYCERIDEMIA concentrations in persons with moderate hypertriglyceridemia. Relative to the placebo treatment, fasting triglycerides were reduced by 27% after the 3.4-g/d dose, consistent with previous reports (12,(42)(43)(44)(45)(46). The percentage reduction achieved was related to the subjects' triglyceride concentrations after the placebo dose so that, on average, the subjects with the highest triglycerides achieved the greatest percentage reduction after the higher dose.…”
Section: Discussionsupporting
confidence: 77%
“…The findings of this meta-regression analysis were supported by studies in patients with essential hypertension, 47,93 hypertriglyceridemia, 57 or combined hyperlipidemia, 44,94 patients who had undergone heart transplantation, 95 or hypertensive heart transplant recipients, 48 showing significant reductions in systolic and/or diastolic BP with omega-3 EE given at 2000-6000 mg/day. The reduction of BP may be due to effects on the arterial vascular bed.…”
Section: Blood Pressuresupporting
confidence: 48%
“…20 Omega-3 EE oral administration in healthy volunteers for 12 weeks determined significant dosedependent increases in plasma phospholipid EPA and DHA content. 43 The same increases in plasma/serum phospholipid EPA and DHA content were seen in various patient populations receiving oral omega-3 EE, such as those with combined hyperlipidemia, 44 severe hypertriglyceridemia, 45 CAD, 46 essential hypertension, 47 and hypertensive heart transplant recipients. 48 EPA and DHA concentrations in plasma phospholipids are related to the level of EPA and DHA incorporated into cell membranes.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 69%
“…[35][36][37][38][39][40] This study, and others, has not shown detrimental effects, in healthy volunteers, hypertensive or dyslipidaemic subjects or those with diabetes. 36,41,42 In obese hyperinsulinaemic women, we found there are no adverse effects of LC n-3 PUFA on glucose, HbA1c or insulin sensitivity either during weight-loss or in a stable weightreduced state. Moreover, there was a significant reduction glucose excursion during the OGTT in both the WLFO and WLPO groups.…”
Section: Discussionmentioning
confidence: 69%